2012
DOI: 10.1107/s1744309112037529
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and preliminary X-ray diffraction analysis of the RNA-dependent RNA polymerase fromThosea asignavirus

Abstract: Thosea asigna virus (TaV) is a positive-sense, single-stranded RNA (ssRNA) virus that belongs to the Permutotetravirus genera within the recently created Permutotetraviridae family. The genome of TaV consists of an RNA segment of about 5.700 nucleotides with two open reading frames, encoding for the replicase and capsid protein. The particular TaV replicase does not contain N7-methyl transferase and helicase domains but includes a structurally unique RNA-dependent RNA polymerase (RdRp) with a sequence permut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The full-length TaV ORF1 (140 kDa) fused to an N-terminal tail containing an hexa-histidine Tag (TaV rORF1; Fig 1A ) was expressed in Hi5 insect cells infected with a recombinant baculovirus, rBV-TaV ORF1. After expression, the recombinant protein was rapidly cleaved releasing a 75 kDa protein fragment ( Fig 1B ) [ 13 ]. Mass spectrometry (MALDI-TOF/TOF) showed that this polypeptide harbors the first 674 residues of the recombinant protein, including the whole RdRP domain (TaV pol from here on; Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full-length TaV ORF1 (140 kDa) fused to an N-terminal tail containing an hexa-histidine Tag (TaV rORF1; Fig 1A ) was expressed in Hi5 insect cells infected with a recombinant baculovirus, rBV-TaV ORF1. After expression, the recombinant protein was rapidly cleaved releasing a 75 kDa protein fragment ( Fig 1B ) [ 13 ]. Mass spectrometry (MALDI-TOF/TOF) showed that this polypeptide harbors the first 674 residues of the recombinant protein, including the whole RdRP domain (TaV pol from here on; Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of TaV pol was solved by SAD methods from Lu 3+ derivative co-crystals to 3.0 Å resolution ( Table 1 ) [ 13 ]. Native data was then used to complete and refine the model to a final resolution of 2.15 Å ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). The only exception to this scheme is found in Birnavirus and Permutatetravirus polymerases, where motif C is encoded upstream of motif A (Garriga et al, 2007;Ferrero et al, 2012). Each of the seven motifs in the RNA polymerase domain adopts a specific fold that extends beyond the regions of sequence similarity into the so-called homomorphs for most RNA virus RNA polymerases (Lang et al, 2013).…”
Section: Rna-dependent Rna Polymerasesmentioning
confidence: 99%